Islamic Law, International Inheritances, and Ottoman Subjecthood in Early Modern Istanbul - Stefini, Tommaso (Islamic law and society, 2026)
This article analyzes disputes over inheritance between Venetian merchants and Ottoman subjects in seventeenth-century Istanbul. Despite religious prohibitions and the admonitions of ambassadors, Venetians residing in Ottoman cities sometimes married Ottoman Christian women in Islamic courts. If the Venetian husband died in Ottoman territory, the division of his estate might become a source of dispute between his Ottoman and Venetian heirs, leading to a diplomatic controversy. Neither Islamic law nor international agreements (ahidnames) between Venice and the Ottoman Empire provided a clear framework for addressing such controversies. By analyzing two disputes over the estates of deceased Venetians, I demonstrate that the Islamic law of inheritance played a significant role in the emergence of an empire-wide notion of Ottoman state membership in the early modern period.